2016
DOI: 10.1080/15548627.2016.1235122
|View full text |Cite
|
Sign up to set email alerts
|

KSHV reduces autophagy in THP-1 cells and in differentiating monocytes by decreasing CAST/calpastatin and ATG5 expression

Abstract: We have previously shown that Kaposi sarcoma-associated herpesvirus (KSHV) impairs monocyte differentiation into dendritic cells (DCs). Macroautophagy/autophagy has been reported to be essential in such a differentiating process. Here we extended these studies and found that the impairment of DC formation by KSHV occurs through autophagy inhibition. KSHV indeed reduces CAST (calpastatin) and consequently decreases ATG5 expression in both THP-1 monocytoid cells and primary monocytes. We unveiled a new mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 101 publications
2
31
0
Order By: Relevance
“…It has been reported that autophagy, induced by CSF2/ GM-CSF (colony stimulating factor 2), is essential for proper monocyte in vitro differentiation into DCs [15]. Consistent with these results, we have recently shown that KSHV, as well as other completely unrelated oncoviruses such as hepatitis C virus (HCV), reduced autophagy to impair DC formation [12,16,17], although through different strategies.…”
Section: Introductionsupporting
confidence: 84%
See 2 more Smart Citations
“…It has been reported that autophagy, induced by CSF2/ GM-CSF (colony stimulating factor 2), is essential for proper monocyte in vitro differentiation into DCs [15]. Consistent with these results, we have recently shown that KSHV, as well as other completely unrelated oncoviruses such as hepatitis C virus (HCV), reduced autophagy to impair DC formation [12,16,17], although through different strategies.…”
Section: Introductionsupporting
confidence: 84%
“…Autophagy, induced by CSF2 has been reported to be essential for monocyte differentiation into DCs [15]. Since EBV interferes with the autophagic process in other cell types [37] and autophagy inhibition by other oncoviruses results in an impairment of the differentiation process in infected monocytes [12,17], we investigated whether the reduction of DC formation mediated by EBV could correlate with autophagy inhibition. As shown in Figure 3(a), the expression level of the autophagic marker MAP1LC3-II/LC3-II (microtubule associated protein 1 light chain 3)-II was reduced in the presence of bafilomycin A 1 (BAF) [38] in a time-dependent fashion in EBV-infected monocytes compared to the mock control cells, indicating that the autophagic flux was reduced by EBVinfection.…”
Section: Ebv Reduces Autophagy In Differentiating Monocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it has been reported that JNK activation stimulates the autophagy by interfering with Bcl-2/Beclin interaction and that the pharmacological inhibition of JNK causes accumulation of p62 and reduces the LC3II/LC3I ratio flux and activates caspase 3. In particular, p54 JNK phosphorylation may support cell survival during cellular stress, while viral infections such as Kaposi sarcoma-associated herpes virus infections are able to inhibit p54 JNK phosphorylation, thus inhibiting autophagy and reducing cell survival [67–69]. In agreement with these results, the inhibition of p54 JNK phosphorylation by CUR further supports the block of the autophagic flux and the induction of apoptosis in MM cells.…”
Section: Discussionsupporting
confidence: 54%
“…Monocytes were isolated from human PBMCs of healthy donors as previously described and infected with 293‐EBV supernatants from 293/EBV cells containing recombinant B95‐8 virus obtained as previously described . In some experiments, B lymphocytes isolated from human peripheral blood mononuclear cells by using anti‐CD19 monoclonal antibody‐conjugated magnetic microbeads (130‐050‐301; Miltenyi Biotec, Bergisch Gladbach, Germany) were exposed to EBV as above reported for monocytes.…”
Section: Methodsmentioning
confidence: 99%